Peran Media Instagram Dinas Perdagangan Koperasi Usaha Kecil dan Menengah Kabupaten Demak sebagai Sumber Informasi Pegawai - Yusuf Lukman Hakim; Suryanto Suryanto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to find out how Instagram is used by the Demak Regency Trade, Cooperatives, Small and Medium Enterprises Office as a source of information for employees. The research uses a qualitative method with a case study approach conducted from 1–30 August 2025. Data was obtained through interviews, observations, and documentation of the agency's Instagram account. The results of the study show that Instagram is used as a means of publishing official activities and information, but it is not optimal due to limited human resources, a long upload process, and monotonous content. Based on the theory of Uses and Gratifications and Media Richness Theory, the effectiveness of digital communication requires the ability to present interesting and relevant information so that the message conveyed can meet the needs of internal audiences. Other findings show that some employees have not made Instagram the main source of information due to a lack of content updates and a lack of visual variation. Therefore, it is recommended that social media management be carried out more professionally through improving admin competence, content calendar planning, and better internal coordination to ensure the consistency and quality of published information. Thus, Instagram can function more optimally as an official communication medium.